1999
DOI: 10.1128/aac.43.4.868
|View full text |Cite
|
Sign up to set email alerts
|

Impact ofgyrAandparCMutations on Quinolone Resistance, Doubling Time, and Supercoiling Degree ofEscherichia coli

Abstract: Isogenic mutants derived from quinolone-susceptible isolate WT by introducing gyrA (S83L, D87G) and parC (S80I, E84K) mutations associated with quinolone resistance were characterized with respect to quinolone resistance, growth rate, and degree of global supercoiling. The latter was determined by use of a pair of reporter plasmids carrying supercoiling-dependent promoters pgyrA and ptopA, respectively, transcriptionally fused to the reporter gene bla coding for TEM-1 ␤-lactamase. The quotient (Qsc) of the ␤-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
91
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(108 citation statements)
references
References 56 publications
(80 reference statements)
8
91
1
1
Order By: Relevance
“…High-level mutants were not detected at low drug concentrations with sample sizes of 10-30; thus, under these conditions, low-level resistance mutants were much more abundant than high-level ones. Although selection of resistant pathogens is likely to be more complex in patients than in the laboratory [30], our data collectively suggest that the recovery of many types of M. tuberculosis mutants from patients [4,13] reflects treatment with low-to-moderate concentrations of fluoroquinolone.…”
Section: Discussionmentioning
confidence: 85%
“…High-level mutants were not detected at low drug concentrations with sample sizes of 10-30; thus, under these conditions, low-level resistance mutants were much more abundant than high-level ones. Although selection of resistant pathogens is likely to be more complex in patients than in the laboratory [30], our data collectively suggest that the recovery of many types of M. tuberculosis mutants from patients [4,13] reflects treatment with low-to-moderate concentrations of fluoroquinolone.…”
Section: Discussionmentioning
confidence: 85%
“…The results correlated well with their quinolone/fluoroquinolone resistance profiles. Salmonella Typhimurium ST20751, S. Heidelberg 22396 and S. Enteritidis 17929R and 17929N that were resistant to nalidixic acid and ciprofloxacin and/or enrofloxacin all had an amino acid substitution at codon 87 (Asp87Asn), which has been widely reported in previous studies [25].…”
Section: Discussionmentioning
confidence: 93%
“…The molecular investigations into the underlying quinolone resistance mechanisms revealed that all quinolone-resistant isolates possessed the typical mutations in the topoisomerase genes, gyrA and parC , reported by other studies (39,40). Although quinolone resistance results mostly from chromosomal mutations, it may also be mediated by a plasmid-encoded qnr gene in members of the family Enterobacteriaceae (41).…”
Section: Discussionmentioning
confidence: 95%